The international order and autocratization - Kneuer, Marianne; Demmelhuber, Thomas (The Routledge Handbook of Autocratization, 2024)
Within the vivid scholarly debate on autocratization, this chapter focuses on the international order. The contribution is guided by two assumptions: First, autocratization does not take place in an isolated way as a domestic development but is rather interwoven with regional and global dynamics interacting with norms, rules, and institutions that are part of the international order (IO). Second, autocratization is impacted by different international factors. We identify four main structural factors that impact autocratization dynamics: (1) external shocks, (2) the normative foundations and conjunctures of the IO (also reflected in the zeitgeist), (3) multipolarity and regional dynamics, (4) and diffusion. This allows us to present different pathways of autocratization on the domestic level.
CRIS-Team Scopus Importer:2024-06-14